ANALISIS IMPLEMENTASI STANDAR ISI DALAM KURIKULUM SDIT : MENGINTEGRASI NILAI AGAMA DAN AKADEMIK UNTUK PEMBENTUKAN KARAKTER - Merri Yelliza (STKIP Subang, 2025)
This study examines the implementation of the content standards in the curriculum at SDIT ADZKIA 2, which integrates Islamic education with general subjects. The aim of this research is to explore how this curriculum is applied and to identify the challenges faced. A qualitative approach was used, involving interviews and observations, with thematic analysis of the collected data. The findings indicate that the implementation of content standards that integrate Islamic values with academic knowledge has a positive impact on academic achievement and character development. However, challenges such as limited time, resources, and teacher training affect its effectiveness. This study recommends enhanced collaboration between religious and general education teachers, as well as more in-depth training for teachers to achieve holistic education.